2016
DOI: 10.1007/s40674-016-0034-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Treatment of Bone Disease in Systemic Lupus Erythematosus

Abstract: Opinion statementSystemic lupus erythematosus (SLE), an autoimmune chronic inflammatory disease, can be associated with significant morbidity and mortality of which bone disease such as osteoporosis is a contributor. Patients with SLE are at risk for low bone mineral density (BMD) due to a variety of reasons including inflammation, glucocorticoid use, vitamin D deficiency, premature ovarian failure, increased damage, and traditional risk factors such as age and gender. With better treatments for SLE, survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…[31] In addition, long-term use of corticosteroids may induce osteoporosis in patients with SLE by affecting their bone turnover, increasing bone resorption and decreasing bone formation, preventing the formation of collagen and osteocalcin as well as affecting the bone matrix mineralization. [32] Recent studies have shown that low-dose vitamin D and calcium supplementation (<1000 IU vitamin D and <800 mg calcium) does not improve BMD in pediatric SLE patients. [3334] However, long-term supplementation with different doses of vitamin D (400–1200 IU) and calcium (1–1.5 g) can have a better effect on the BMD of postmenopausal osteoporotic women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31] In addition, long-term use of corticosteroids may induce osteoporosis in patients with SLE by affecting their bone turnover, increasing bone resorption and decreasing bone formation, preventing the formation of collagen and osteocalcin as well as affecting the bone matrix mineralization. [32] Recent studies have shown that low-dose vitamin D and calcium supplementation (<1000 IU vitamin D and <800 mg calcium) does not improve BMD in pediatric SLE patients. [3334] However, long-term supplementation with different doses of vitamin D (400–1200 IU) and calcium (1–1.5 g) can have a better effect on the BMD of postmenopausal osteoporotic women.…”
Section: Discussionmentioning
confidence: 99%
“…[36] In addition, a high calcium supplementation may improve the bone matrix and, consequently, prevent its destruction. [32]…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is reported that SLE itself is associated with low BMD or osteoporosis (Pineau et al, 2004) (Tang et al, 2013) (Sun et al, 2015). There are some reasons such as inflammation, vitamin D deficiency, and premature ovarian failure for risk of low BMD (Lin & Grossman, 2016). Those mechanisms are occurred in other rheumatic diseases than SLE and may also contribute to very high frequency of fragility fracture in this study.…”
Section: Discussionmentioning
confidence: 99%